The relationship of social networks, coordination and business performance of grocery retail SMEs in Malaysia: the moderating effect of business adaptation strategies / Nor Asmahani Ibrahim - Ibrahim, Nor Asmahani (2021)
Many small medium enterprises (SMEs) including grocery retail businesses in Malaysia are facing tough competitive business environment that is demanding them to strategist effectively for business survival and ensure sustainability. Malaysian grocery retail SMEs are struggling to keep their business alive as the growth of new stores and modern retail formats have affected them with more and more customers turning to bigger and more established retailers. In the face of such competition, grocery retail SMEs in Malaysia is pushed to collaborative avenues that will enable them to establish their presence in the industry. One such call is for grocery retail SMEs to look at their social networks and coordination efforts as a means of establishing fruitful business relationships. On another note, being adaptive is also vital for grocery retail SMEs to remain competitive in the business. Therefore, this study aims to examine the social network practices and coordination efforts on business performance of grocery retail SMEs. This study also aims to examine the moderating effect of business adaptation strategies on the social networks and coordination efforts on business performance of grocery retail SMEs. Social network was measured by the dimensions of homophily and propinquity. Coordination was measured by information exchange, communication and partnering while business performance used qualitative measures of customer loyalty and competitive advantage. The findings of the research indicated that business adaptation strategies and coordination had significant effect on business performance. The results are useful especially to Malaysian grocery retail SMEs to better understand the importance of business adaptation strategies and coordination efforts to enhance business performance through customer loyalty and competitive advantage. Coordination through communication, partnering and information exchange are important for supply chain members to ensure superior business performance through customer loyalty and competitive advantage. However, social network was not found to affect business performance significantly. This was in contrast to existing literature but rationally this can be attributed to the business networks that are not controlled by social relationships. The findings also indicated that business adaptation strategies do not moderate the relationship between social networks and coordination on business performance of grocery retail SMEs. Therefore, studies on the characteristics of social networks and understanding their effect on business performance must be extended since it showed contradictory findings even though social networks are extensively used in Western countries and in Chinese’ business networks. It is recommended that future studies address the application of business adaptation strategies, coordination efforts and social network in other business situations and industrial settings and determine whether business adaptation strategies have intervening effects on other aspects of business performance.